Rape Myth Acceptance Among College Students in the United States, Japan, and India. (November 2016) - Stephens, Tamara; Kamimura, Akiko; Yamawaki, Niwako; Bhattacharya, Haimanti; Mo, Wenjing; Birkholz, Ryan; Makomenaw, Angie; Olson, Lenora M.
Rape myth acceptance is an important determinant of sexual assault behaviors. This study explored country and gender differences in rape myth acceptance among undergraduate students in the United States, Japan, and India. Male and female college students ( N = 637) in these three countries participated in a self-administered survey in the fall of 2012 (the United States, n = 206; Japan, n = 215; and India, n = 216). The order of the countries arranged in increasing order of likelihood of disbelieving rape claim was as follows: the United States, Japan, and India. U.S. and Japanese students were less likely to disbelieve rape claims ( p < .01) while U.S. students also were less likely to believe that victims are responsible for rape ( p < .01). Overall, female participants were less likely to believe in the rape myth acceptance, disbelief of rape claim and victims are responsible for rape ( p < .05). Acceptance of rape myth also varied by whether a participant knew about an organization or who do not believe they would seek help for sexual assault. Non-help seeking is associated with rape myth acceptance. This study, which used the same survey and data collection methods, provides comparative information on rape myth acceptance among college students in the United States, Japan, and India, which is not otherwise available, and contributes to providing fundamental knowledge to develop country-specific prevention programs.